Penggunaan Media Sosial Untuk Pemasaran Produk Kerajinan Tangan di Kelurahan Bentiring Kota Bengkulu - Esti Pasaribu; Retno Agustina Ekaputri; Yusnida; Yefriza; Novi Tri Putri; Septriani (UNIB Press, 2023)
Women have a big role in the economy, especially during the pandemic covid-19. In this situation, many people can not stand in normal way for selling and buying. The others lost their jobs because the economy were not running well. For this reason, it is necessary to carry out Community Service (PPM) by taking place in the Bentiring Village, Bengkulu City. Activities was carried out in November 2020 not only by providing training on making handicraft accessories but also facilitating them to sell it online using social media. The participants of this activity is representatives of housewives. Online marketing of handicraft accessories will help the community in increasing family income during the pandemic.